2009
DOI: 10.1513/pats.200808-078rm
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Actin-Myosin-Actin Connectivity in Airway Smooth Muscle as a Treatment for Asthma?

Abstract: Breathing is known to functionally antagonize bronchoconstriction caused by airway muscle contraction. During breathing, tidal lung inflation generates force fluctuations that are transmitted to the contracted airway muscle. In vitro, experimental application of force fluctuations to contracted airway smooth muscle strips causes them to relengthen. Such force fluctuation-induced relengthening (FFIR) likely represents the mechanism by which breathing antagonizes bronchoconstriction. Thus, understanding the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
3
32
0
1
Order By: Relevance
“…Our system could also be used to study the bronchoprotective effect of deep inspiration observed in people (66). Because the airways remain within their native architecture, and because fluctuationinduced relengthening has molecular determinants that differ from those of isometric force (9,(14)(15)(16)(17), it may be a useful platform for discovering novel pharmacologic agents that potentiate breathing-induced airway dilatation (67). For example, we have previously shown that latrunculin B (14), dexamethasone (17), and mitogen-activated protein kinase kinase inhibition (15) potentiate force fluctuation-induced relengthening of contracted canine tracheal smooth muscle strips, and unpublished observations in our laboratory suggest that latrunculin B potentiates breathinginduced reversal of bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Our system could also be used to study the bronchoprotective effect of deep inspiration observed in people (66). Because the airways remain within their native architecture, and because fluctuationinduced relengthening has molecular determinants that differ from those of isometric force (9,(14)(15)(16)(17), it may be a useful platform for discovering novel pharmacologic agents that potentiate breathing-induced airway dilatation (67). For example, we have previously shown that latrunculin B (14), dexamethasone (17), and mitogen-activated protein kinase kinase inhibition (15) potentiate force fluctuation-induced relengthening of contracted canine tracheal smooth muscle strips, and unpublished observations in our laboratory suggest that latrunculin B potentiates breathinginduced reversal of bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that the force produced by ASM in response to a given stimulus is greater in a static environment than a dynamic environment. Oscillating strains at amplitude that is thought to prevail in vivo during breathing maneuvers also caused elongation of the contracted muscle (128,130,160). This later phenomenon is now referred to as force fluctuation-induced relengthening (FFIR).…”
Section: Muscle Factorsmentioning
confidence: 99%
“…The mechanisms underlying FFIR are not well understood but the length of the actin filaments seems to play a role (160). Collectively, these studies have shown that the force (66,84,85,128,186,198,242) and the stiffness (66,84,128,198) of ASM, as well as the length of the contracted ASM (128,130,160,186), are affected by length oscillations (66,84,85,128,130,160,186,198,242) or simply by an acute stretch (242). Considering these phenomena together, one can envision the following in vivo vicious cycle.…”
Section: Muscle Factorsmentioning
confidence: 99%
“…Other changes in asthmatic ASM cells may reside in the filamentous organization of the contractile apparatus as it has been proposed that the myosin thick filaments are less prone to disruption following mechanical strain 4,17 . Additionally, there is evidence that actin filament polymerization may underlie the altered behaviour of asthmatic ASM 18,19 . In this case, whereas mechanical stretch leads to shortening actin filaments and derangement of myosin filament assembly, in asthmatic ASM longer actin filaments are associated with refractoriness of thick myosin filament derangement following mechanical stretch, thus supporting greater force-generating capacity.…”
mentioning
confidence: 99%
“…Other changes in asthmatic ASM cells may reside in the filamentous organization of the contractile apparatus as it has been proposed that the myosin thick filaments are less prone to disruption following mechanical strain 4,17 . Additionally, there is evidence that actin filament polymerization may underlie the altered behaviour of asthmatic ASM 18,19 . We have shown that WNT-5A protein expression is increased in ASM cells isolated from asthmatics compared to non-asthmatic individuals 23 and WNT-5A expression has been associated with Th2-high asthma 24 .…”
mentioning
confidence: 99%